Adenoid cystic carcinoma of uterine cervix in a young patient - Seth Ankit; Agarwal Asha (Wolters Kluwer Medknow Publications, 2009)
Adenoid cystic carcinoma of uterine cervix is a rare tumor. Its origin is debatable. It has a high incidence in postmenopausal women but rarely can develop in patients under 40. An association with squamous cell carcinoma has been described. We report a case of adenoid cystic carcinoma of the endocervical canal with foci of squamous cell carcinoma in a 34-year-old suffering from menorrhagia associated with blood-stained vaginal discharge. Per vaginum and per speculum examination revealed a growth. Cervical biopsy showed bits of tissue, suggesting adenoid cystic carcinoma. Patient was operated upon and uterus with cervix sent for histopathological examination. We report this case because of its rarity, particularly in young patients, with description of illustrative pathology and discussion on the histological diagnosis.